Bilinguals' Plausibility Judgments for Phrases with a Literal vs. Non-literal Meaning: The Influence of Language Brokering Experience - López, Belem G.; Vaid, Jyotsna; Tosun, Sümeyra; Rao, Chaitra (Frontiers in Psychology, 2017)
Previous work has shown that prior experience in language brokering (informal translation) may facilitate the processing of meaning within and across language boundaries. The present investigation examined the influence of brokering on bilinguals’ processing of two word collocations with either a literal or a figurative meaning in each language. Proficient Spanish-English bilinguals classified as brokers or non-brokers were asked to judge if adjective+noun phrases presented in each language made sense or not. Phrases with a literal meaning (e.g., stinging insect) were interspersed with phrases with a figurative meaning (e.g., stinging insult) and nonsensical phrases (e.g., stinging picnic). It was hypothesized that plausibility judgments would be facilitated for literal relative to figurative meanings in each language but that experience in language brokering would be associated with a more equivalent pattern of responding across languages. These predictions were confirmed. The findings add to the body of empirical work on individual differences in language processing in bilinguals associated with prior language brokering experience.